Virucidal and virostatic in vitro activity of ELOM-080 against respiratory pathogens - Jörn Thomsen; Kristina Röschmann-Doose; Thomas Wittig; Karin Kraft (Elsevier, 2021)
Background: The herbal medicinal product (HMP) ELOM-080 has a proven efficacy in the treatment of acute respiratory tract (ART) infections, which typically are of viral etiology. However, whether the HMP exerts an antiviral activity against viral pathogens was unknown and therefore tested in this in vitro study. Purpose: This study was performed in order to test antiviral effects of the HMP against four viral pathogens of ART infections: Influenza A (FluA), Rhinovirus (RV), Respiratory Syncytial Virus (RSV), and Adenovirus (AV). Methods: Infectivity of the viruses was tested after their 2 or 24 h incubation with HMP at final concentrations between 89 and 2673 µg ml−1 in order to investigate virucidal activity. Virostatic effects were assessed by application of physiologically tolerated concentrations up to 268 µg ml−1 in cell cultures 1 h after infection with each virus and quantification of plaque formation or cytopathogenic effect. Results: HMP inhibited infectivity of FluA, RV and RSV by more than 50%, and of AV by about 20%. In the virostatic tests, mean half maximal effective concentrations (EC50) for RNA viruses were almost 15 times lower compared to virucidal results, AV was not significantly affected. Discussions: The in vitro antiviral effects of ELOM-080 on the enveloped viruses FluA and RSV suggest that this HMP exerts permanent and/or transient viral envelope changes, thereby potentially lowering the attachment to the host cell membrane. Furthermore, the rather high sensitivity of RNA viruses for the HMP suggests an effect on integrity and functionality of viral RNA which may interfere with viral replication causing the observed virostatic effects.